Proposta de um ambiente multiagente para a monitoração analítica de indicadores gerenciais e de apoio à decisão para uma empresa do setor elétrico - Reis, Vinícius Ataídes (2018)
Decision support and management indicator are fundamental inputs to make good planning and, for consequence, a good management of the operational processes in a company. Nowadays, the electrical sector companies in the Brazil have almost all the operational activities automated. However, the monitoring of all these activities is manual and requires a lot of time for manipulation and preparation by the managers of the information. This work proposes a solution based in a multiagent environment to create an analytical monitoring system. The solution aims to verify the performance of an organizational process from automatic analyzes of its indicators. The monitoring permits identify problems and apply corrective actions as soon as possible. To implement the proposed solution, this work proposes a customization of the management indicator system of the company. The paper shows the proposed multiagent architecture to execute the performance analyzes of the processes. Beside this, the paper shows the computational implementation as from evolutionary maintenances in the management indicator system. To show the effectiveness of the created solution, this paper presents some examples of how to create an analytical monitoring in it. Two case studies are carried out, detailing the construction of the solution and the monitoring process in the environment, allowing the reader to evaluate how much the proposed approach is efficient. The practical results obtained demonstrate the success of the work. Finally, work concludes that proposed approach reaches the project objectives.